2014
DOI: 10.1109/tbme.2013.2287245
|View full text |Cite
|
Sign up to set email alerts
|

Combining Motor Imagery With Selective Sensation Toward a Hybrid-Modality BCI

Abstract: A hybrid modality brain-computer interface (BCI) is proposed in this paper, which combines motor imagery with selective sensation to enhance the discrimination between left and right mental tasks, e.g., the classification between left/ right stimulation sensation and right/ left motor imagery. In this paradigm, wearable vibrotactile rings are used to stimulate both the skin on both wrists. Subjects are required to perform the mental tasks according to the randomly presented cues (i.e., left hand motor imagery,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
66
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(68 citation statements)
references
References 48 publications
2
66
0
Order By: Relevance
“…In this study, the stimulation parameters were slightly different across subjects due to different wrist size. Such difference have shown to have limited influence for current tactile BCI performance and ERD/ERS dynamics [34], [35], [54]. Stimuli parameters, such as amplitude and frequency, and their correlation with ERD/ERS dynamics could be the topic of a future study, with the goal of further enhancing the performance tactile BCI.…”
Section: T1 (Ss-l Vs Ss-r Vs Ss-b) T2 (Ss-l Vs Ss-r Vs Ss-s) T3 (Ss-lmentioning
confidence: 99%
“…In this study, the stimulation parameters were slightly different across subjects due to different wrist size. Such difference have shown to have limited influence for current tactile BCI performance and ERD/ERS dynamics [34], [35], [54]. Stimuli parameters, such as amplitude and frequency, and their correlation with ERD/ERS dynamics could be the topic of a future study, with the goal of further enhancing the performance tactile BCI.…”
Section: T1 (Ss-l Vs Ss-r Vs Ss-b) T2 (Ss-l Vs Ss-r Vs Ss-s) T3 (Ss-lmentioning
confidence: 99%
“…With the advantage of subjective motor intention decoding, this independent BCI modality has attracted extensive interest [8]- [11]. In addition, it has been shown that brain response evoked (transient and steady-state potential) or induced (oscillatory power) by exogenous stimuli can facilitate voluntary attention decoding, resulting in at least three BCI categories: (A) transient BCI [12]- [14], such as the visual P300-based speller; (B) steady-state BCI [15]- [17], such as the steady-state visual evoked potentials (SSVEP); and (C) oscillatory BCI [18], [19], such as the tactile BCI based on stimulus-induced oscillatory dynamics. The diversity of BCI modalities may offer alternative methods when a selected modality fails in achieving an adequate performance.…”
mentioning
confidence: 99%
“…Recently, in a series of studies, we proposed a tactile BCI based on oscillatory dynamics from the somatosensory area of the cortex, which we termed selective sensation (SS) tactile BCI [18], [19], [40], [41]. This approach is based on the observation that mental processing of afferent inflow in the human somatosensory system also induces ERD/ERS [42], [43] [44].…”
mentioning
confidence: 99%
“…This system achieved a mean accuracy of 72% in 11 subjects, when selecting between two targets. By comparison, we have shown that BCI based on tactile selective sensation has largely increased tactile BCI performance by approximately 10%, and this tactile BCI modality based on SS substantially outperformed previous tactile BCI systems, making it potentially applicable to a larger number of users [36], [37]. The ERD/ERS oscillatory response and SSSEP response provide complementary information of the somatosensory input processing.…”
Section: Discussionmentioning
confidence: 92%